Improving IS quality in IS outsourcing - Kissiov, Slav (fi=Turun yliopisto. Turun kauppakorkeakoulu|en=University of Turku. Turku School of Economics|, 2016)
The goal of this paper is to evaluate a complex information system delivered to a customer. The author of this paper spent four months at a company while writing this thesis. A single case study was selected as the most appropriate research method for this report. The research was carried out by adapting the famous DeLone and McLean model of IS success to the perspective of this paper. The research carried out comprised primary and secondary data collection. Besides verifying three of the relationships originally proposed by D&M, this paper introduces a previously unexplored relationship among two of the variables (Service Quality  System Quality). Furthermore, in the course of research it became evident that the variables selected, were not enough to capture the full extent of IS success in the context of outsourcing. IT governance was found to be of paramount importance to IS success. This is why this thesis suggests that IT governance is added as a variable to research models of IS success when investigating an outsourcing case. Alternatively, practitioners are advice to emphasize on the importance of IT governance in outsourcing relationships.